Exercise-downregulated CD300E acted as a negative prognostic implication and tumor-promoted role in pan-cancer - Luo, Zhiwen; Zhu, Jinguo; Xu, Rui; Wan, Renwen; He, Yanwei; Chen, Yisheng; Wang, Qing; Chen, Shuo; Chen, Shiyi (Frontiers in Immunology, 2024)
Background: Breast cancer ranks as one of the most prevalent malignancies among women globally, with increasing incidence rates. Physical activity, particularly exercise, has emerged as a potentially significant modifier of cancer prognosis, influencing tumor biology and patient outcomes.Methods: Using a murine breast cancer model, we established a control and an exercise group, where the latter was subjected to 21 days of voluntary running. RNA Sequencing, bioinformatics analysis, pan-cancer analysis, and cell experiments were performed to validate the underlying mechanisms.We observed that exercise significantly reduced tumor size and weight, without notable changes in body weight, suggesting that physical activity can modulate tumor dynamics. mRNA sequencing post-exercise revealed substantial downregulation of CD300E in the exercise group, accompanied by alterations in critical pathways such as MicroRNAs in cancers and the Calcium signaling pathway. Expanding our analysis to a broader cancer spectrum, CD300E demonstrated significant expression variability across multiple cancer types, with pronounced upregulation in myeloma, ovarian, lung, and colorectal cancers. This upregulation was correlated with poorer prognostic outcomes, emphasizing CD300E's potential role as a prognostic marker and therapeutic target. Moreover, CD300E expression was associated with cancer cell proliferation and apoptosis.The study highlights the dual role of exercise in modulating gene expression relevant to tumor growth and the potential of CD300E as a target in cancer therapeutics. Further research is encouraged to explore the mechanisms by which exercise and CD300E influence cancer progression and to develop targeted strategies that could enhance patient outcomes in clinical settings.